Performance outcomes and their associations with network measures during FIFA World Cup 2018 - Clemente, F. M. (International Journal of Performance Analysis in Sport, 2018)
This study aimed to test the relationships between performance outcomes and network measures of the teams that participated in FIFA World Cup 2018 matches. It was also an aim to compare the performance outcomes and network measures of winners and losers and to compare them for both close and unbalanced scores. A total of 64 matches and 32 teams were observed and coded during this study. Matches were observed and coded, based on the following performance outcomes: scored goals, goals against and shots. Passing distribution was also collected. The network measures were calculated based on passing distribution matrices. Clear large correlations were found between shots and total arcs (0.53, [0.16;0.77]) and density (0.54, [0.18;0.77]) in drawn matches. Clear moderate correlations were found between shots and total arcs (0.42, [0.22;0.59]) and density (0.43, [0.23;0.60]) in won matches. Comparisons between winners and losers during unbalanced scores revealed very likely moderate increases in scored goals (88.7%, [13.8;213.0]; ES: 1.15, [0.23;2.07]) and dyad reciprocity (36.5%, [9.5;70.1]; ES: 0.69, [0.20;1.18]) in winners during unbalanced matches. This study concludes that general network measures studied are not too sensitive to variations in final score. However, some of them can be associated with performance outcomes, such as shots.